Volatiles Emission by Crotalaria nitens after Insect Attack - Fausto Prada; Elena E. Stashenko; Jairo René Martínez (Molecules, 2021)
Plants are known to increase the emission of volatile organic compounds upon the damage of phytophagous insects. However, very little is known about the composition and temporal dynamics of volatiles released by wild plants of the genus Crotalaria (Fabaceae) attacked with the specialist lepidopteran caterpillar Utetheisa ornatrix (Linnaeus) (Erebidae). In this work, the herbivore-induced plant volatiles (HIPV) emitted by Crotalaria nitens Kunth plants were isolated with solid phase micro-extraction and the conventional purge and trap technique, and their identification was carried out by GC/MS. The poly-dimethylsiloxane/divinylbenzene fiber showed higher affinity for the extraction of apolar compounds (e.g., trans-β-caryophyllene) compared to the Porapak™-Q adsorbent from the purge & trap method that extracted more polar compounds (e.g., trans-nerolidol and indole). The compounds emitted by C. nitens were mainly green leaf volatile substances, terpenoids, aromatics, and aldoximes (isobutyraldoxime and 2-methylbutyraldoxime), whose maximum emission was six hours after the attack. The attack by caterpillars significantly increased the volatile compounds emission in the C. nitens leaves compared to those subjected to mechanical damage. This result indicated that the U. ornatrix caterpillar is responsible for generating a specific response in C. nitens plants. It was demonstrated that HIPVs repelled conspecific moths from attacked plants and favored oviposition in those without damage. The results showed the importance of volatiles in plant–insect interactions, as well as the choice of appropriate extraction and analytical methods for their study.